2012
DOI: 10.21168/rbrh.v17n2.p203-211
|View full text |Cite
|
Sign up to set email alerts
|

Monitoramento do Fitoplâncton para a Qualidade da Água de Abastecimento Público ? Estudo de Caso de Mananciais do Rio Grande do Sul

Abstract: A qualidade da água dos mananciais deve ser monitorada para utilização em abastecimento público. A Portaria nº 518/2004 do Ministério da Saúde estabelece o padrão de potabilidade brasileiro que deve ser seguido pelas empresas e companhias de saneamento. Entre os parâmetros a serem avaliados está a densidade de cianobactérias. Estes organismos, bem como outros grupos fitoplanctônicos, podem gerar problemas para o tratamento da água, como odor, sabor e colmatação de filtros das estações de tratamento de água. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
2
0
3
Order By: Relevance
“…The lower survival recorded in the SC1 and LC treatments is possibly related to factors discussed above, such as cyanobacterial bloom. The emergence of cyanobacteria has negative effects on production (Chellappa et al, 2008; Soares et al, 2004) As some authors report that cyanophytes produce toxins that can be lethal to aquatic animals (Müller & Raya‐Rodriguez, 2012; Soares et al, 2004), in this way, some studies found higher survival rates than those reported in this work, such as Sareban et al (2013), with two cycles per year, obtained an 80% survival rate, and as Balakrishnan et al (2011) working with different stocking densities recorded a survival rate of 82% at the end of the cycle.…”
Section: Discussionmentioning
confidence: 99%
“…The lower survival recorded in the SC1 and LC treatments is possibly related to factors discussed above, such as cyanobacterial bloom. The emergence of cyanobacteria has negative effects on production (Chellappa et al, 2008; Soares et al, 2004) As some authors report that cyanophytes produce toxins that can be lethal to aquatic animals (Müller & Raya‐Rodriguez, 2012; Soares et al, 2004), in this way, some studies found higher survival rates than those reported in this work, such as Sareban et al (2013), with two cycles per year, obtained an 80% survival rate, and as Balakrishnan et al (2011) working with different stocking densities recorded a survival rate of 82% at the end of the cycle.…”
Section: Discussionmentioning
confidence: 99%
“…The number of individuals had significant correlation (p<0.05) between conductivity (r=0.72), turbidity (0.46), alkalinity (r=0.56) and total phosphorus (r=0.47). M. aeruginosa is frequently found in eutrophic environments (REYNOLDS et al, 2002;SANT'ANNA et al, 2004;CHELLAPPA et al, 2009;ROLLAND et al, 2009;WANG et al, 2011;MÜLLER et al, 2012;LIU et al, 2012) and can provoke sanitation issues, mainly due to toxicity (BLACK;YILMAZ;PHLIPS, 2011;REICHWALDT;GHADOUANI, 2012).…”
Section: Relation Between Phytoplankton and Abiotic Factorsmentioning
confidence: 99%
“…A comunidade aquática fitoplanctônica responde rapidamente às alterações ambientais, seja pela redução de espécies, ou pela ocorrência de florações, isto é, aumento da biomassa de uma ou mais espécies presentes no ambiente (MULLER, 2012). O monitoramento das condições físicas, químicas e biológicas é importante, mas a classificação das algas, com suas flutuações no espaço e no tempo, é fundamental para a identificação das épocas favoráveis aos florescimentos e à concentração de toxinas na água (TUNDISI, 2003).…”
Section: ~ 73 ~unclassified